Pemanfaatan Instagram Sebagai Media Promosi Toko Helio ITC Mangga Dua Jakarta Utara: (Studi Kasus Toko Pakaian Wanita @helioshop) - Isna Siskawati; Heti Santika; Rinda Nuningtyas (STAI Publisistik Thawalib Jakarta, 2023)
The purpose of this study was to find out and describe the use of Instagram as a promotional medium for the Helio ITC Mangga Dua North Jakarta women's clothing store. Qualitative research through the Marketing Mix (4P) approach which includes product, price, place, and promotion. Data collection techniques with interviews, observation, and documentation. Research informants are Helio owners and employees. The results of the study show: the form of marketing communication by utilizing Instagram social media through the @helioshop account is going well. Consumers can provide comments and input to accounts through photo or video sharing, Instagram stories, captions, and hashtag features. The advantage of promoting via Instagram lies in conveying messages to consumers using the features available on Instagram, and also connecting the Instagram application with other applications such as TikTok, Shopee, Facebook, and WhatsApp, thereby increasing Helio sales. Meanwhile, the drawback lies in the application which must be updated regularly to get the latest features and is prone to fraud in the name of Helio.